PENERAPAN LATIHAN KEHIDUPAN PRAKTIS ANAK USIA 3- 4 TAHUN - Ayu Fajarwati (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
The purposes of this research are to find out and describe: (1) the process of practical life activities in Right Steps Pancoran, (2) kinds of practical life activities that have been done, (3) the purpose and the advantages of studying the practical life activities, (4) the relation between practical life activities on children and the development of their fine motor skill, and (5) the relation of practical life activities on children and their independency. The subjects of this research are 5 children by the age of three to four years old in Annie Apple class of Right Steps Pancoran. This research employed qualitative method and phenomenology study. The researcher used Mills and Huberman model to analyze the data. Observation, interview, photo/video documentations, and field records were used as the collecting data techniques. The result of the analyses showed, (1) there are two methods that have been used in Right Step Pancoran in applying practical life activities i.e. work cycle and three period lessons, (2) there are some activities that can be done in practical life activity such as transferring, pouring, and cutting, (3) there are purposes and advantages that can develop and stimulate each of the student’s growth aspects, (4) the practical life activities that have been done and focusing on the child’s fine muscle can stimulate the development of the children’s fine motor skill, and (5) the practical life activities that have been done can also stimulate the children’s independency by introducing to the activity that can make the children to be more independent.